Synthesis, Crystal Structure, Catalytic Properties, and Luminescent of a Novel Eu(III) Complex Material with 4-Imidazolecarboxaldehyde-pyridine-2-carbohydrazone - Li-Hua Wang; Lei Liang; Peng-Fei Li (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
A novel Eu(III) complex, [Eu(L)2(H2O)4]·(NO3)·(H2O)4 (1) (H2L = 4-imidazolecarboxaldehyde-pyridine-2-carbohydrazide), was synthesized. Its structure has been characterized by elemental analysis, IR, and X-ray single crystal diffraction analysis. Complex 1 is of orthorhombic, space group Fdd2 with a = 29.471(6) A˚, b = 10.287(2) A˚, c = 24.340(5) A˚, V = 7379(3) A˚3, Z = 8, Mr = 902.58, Dc = 1.625 µg·m-3, µ = 1.789 mm-1, F(000) = 3656, GOOF = 1.099, the final R= 0.0517, ωR= 0.1292 for 3043 observed reflections with I > 2σ(I).  The A3 coupling reaction has been investigated using the complex 1 as catalyst. The luminescent spectrum of the complex 1 gives two weak peaks (448 nm and 491 nm) and two strong peaks (596 nm and 620 nm) from excitation at 279 nm.